Phytotoxic Risk Assessment of Ambient Air Pollution on the Crops Yield in Different Development States in Malaysia - Mohammed, N. I. (universiti sains malaysia, 2000)
During the last years, a number of research findings demonstrated that ambient of air pollution especially ground level ozone has adverse impacts on plants. Ozone can cause significant yield losses on sensitive crops species by contaminating their water intake and nutrient supplies. However, the influence of ozone on vegetation depends on several factors such as doses, development phase of the plants, and their genetic backgrounds. The phytotoxicity of ozone is due to its high oxidative capacity where it can weaken the metabolism of plants and leading to yield reduction in agricultural crops. In some of the developing countries like Malaysia, increasing of motor vehicles leading to the air pollution is the major factor that contributes ozone concentration in the air. The aim of this research is to develope a model to assess the phytotoxic risk of ambient air pollution, develope dose-response relationship between yields of agricultural crop species and air pollution, and to estimate the economical loss in crops yield due to air pollution. This research will be carried out in different states in Perlis, Kedah, and Pulau Pinang. In assessing the phytotoxic risk, an estimation model for ozone will be developed to estimate the accumulated exposure over threshold ozone concentration of 40 nmol mol -1 (AOT40).